Design of a drilling unit for deep-sea stratum drilling robot. Issue 7 (October 2021) - Tian, Z; Chen, J; Zhang, P; Zhu, H; Ruan, D; Ge, Y
Abstract: Marine natural gas hydrate has attracted much attention due to its broad energy prospects. With the deepening of research on natural gas hydrate, researchers have found that the decomposition of natural gas hydrate is an important inducer for many natural disasters. This paper proposes a design idea of a deep-sea stratum drilling robot used in gas hydrate test mining area. It can carry out long-term and effective real-time monitoring of the surrounding terrain and environmental changes. The specific structure and function of each component of the robot are introduced, and the locomotion principle of the drilling robot is elaborated. This paper focuses on a drilling unit as one of the key technologies for developing the robot, and the design of drilling unit of robot will be presented in detail. Then, the feasibility of the robot movement and the effect of the drill bit rotation on the soil are obtained through mechanical analysis and simulation. The work of this paper provides guidelines for the development of deep-sea stratum drilling robot in the future.